Assessment of the Oral Health Impacts of Vaping Compared to Traditional Tobacco Use among adolescent population visiting a teaching hospital in Lucknow city, Uttar Pradesh - Malhotra, Shitanshu; Khan, Sheeba; Bharti, Diksha; Maqbool, Faraz (Journal of Neonatal Surgery, 2025)
Introduction: E-cigarettes deliver nicotine through aerosolized vapor, which users inhale. This method of nicotine delivery has led to perceptions of reduced harm compared to conventional smoking, and many individuals have turned to vaping as a means to quit smoking or as a perceived healthier alternative. Aims & Objectives: The aim of this study is to assess and compare the oral health impacts of e-cigarette use (vaping) and traditional tobacco use among adolescents visiting a teaching hospital in Lucknow city, Uttar Pradesh. Materials & Methods:A cross-sectional study was conducted among the participantswhich were categorized into three groups: those who used electronic cigarettes (vapers), those who used traditional tobacco products (smokers), and those who did not use any tobacco or vaping products (control group). Results: This cross-sectional study provided comprehensive evidence that both traditional cigarette smoking and electronic cigarette use are associated with adverse oral health outcomes, although the severity is greater in traditional cigarette smokers.The analysis showed that both vapers (OR = 2.10, 95% CI = 1.45-3.03, p < 0.001) and smokers (OR = 2.45, 95% CI = 1.72-3.50, p < 0.001) had significantly higher odds of periodontal disease compared to non-users. Conclusion: In summary, this study highlights the significant impact of smoking and vaping on periodontal health and oral mucosal lesions.